Trasplantar el árbol de la sabiduría: malocas, maloqueros urbanos y comunidades de pensamiento en Bogotá - Luisa Fernanda Sánchez (Cahiers des Amériques Latines)
In the current context of indigenous mobility toward the largest cities, Bogotá and their outskirts have been witnesses of the establishment of Amazonian ceremonial houses – malocas – destined to a specific sector of the urban population. In order to reconstruct this process the present article analyzes the reconfiguration of the maloca and of some of it associated elements. Particularly, the figure of the anciano, the interethnic alliances with other native actors and not-natives of the urban setting and the progressive establishment of a distinctive group of “ethnic entrepreneurs” inside the indigenous community Uitoto resident in the city. The interaction among these actors questions the traditional image of the native, image that today seems to be dissolved to create a new spectrum of identification possibilities.